BRAF Mutation Status in Primary, Recurrent, and Metastatic Malignant Melanoma and Its Relation to Histopathological Parameters - Aris Spathis; Alexander C Katoulis; Vasileia Damaskou; Aikaterini I. Liakou; Christine Kottaridi; Danai Leventakou; Dimitrios Sgouros; Andreas Mamantopoulos; Dimitrios Rigopoulos; Petros Karakitsos; Ioannis G. Panayiotides (Mattioli1885, 2019)
Background: BRAF mutations are a common finding in malignant melanoma (MM). Nevertheless, apart from their significance as a therapeutic target in advanced melanoma, their prognostic value is still debated. Objective: To assess BRAF mutation status in primary, recurrent, or metastatic MM and its correlations with histopathological findings. Methods: We analyzed 203 samples from 178 consecutive patients: 129 primary cutaneous MM, 49 metastatic and recurrent MM of unknown primary site, and 25 cases of recurrences or metastases of primary MM. BRAF mutations in exon 15 were identified with real-time polymerase chain reaction and/or direct sequencing or pyrosequencing. Histopathological examination was performed according to standard procedures. Results: We observed a 42.1% prevalence of BRAF mutations at codon 600 among our patients, 84% of whom harbored the V600E mutation. Mutations showed a statistically significant increase in younger patients (P = 0.011), in ulcerated tumors (P = 0.020), and in tumors lacking solar elastosis in adjacent dermis (P = 0.008). Mutations were also more common in male patients, as well as in primary MMs of the torso, and in nonvisceral metastases, however without reaching statistical significance. Logistic regression analysis identified type and ulceration as the only significant predictors of BRAF mutation. The highest frequencies of mutated BRAF were identified in superficial spreading and nodular types, and the lowest in acral lentiginous and lentigo maligna types. In situ MM and primary dermal melanoma displayed intermediate frequencies. Conclusion: Frequency of mutated BRAF is type-related and correlated with ulceration, a known adverse prognostic factor.